Revealing and modulating catalyst reconstruction for highly efficient electrosynthesis of ammonia - Xinyue Shi; Wei-Hsiang Huang; Ju Rong; Minghui Xie; Qingbo Wa; Ping Zhang; Hainan Wei; Huangyu Zhou; Min-Hsin Yeh; Chih-Wen Pao; Jie Wang; Zhiwei Hu; et al. (Nature Communications)
Abstract Electrocatalytic nitrate reduction (NO3RR) is a promising route for sustainable ammonia synthesis under mild conditions. The widely studied Co-based catalysts undergo significant reconstruction due to nitrate oxidation and electric-field reduction during NO3RR, leading to activity degradation. To address this issue, we develop a Co6Ni4 heterostructured catalyst that consists of interlaced metallic Co and Ni domains. Operando X-ray absorption spectroscopy and other in-situ characterization techniques, in conjunction with theoretical calculations, demonstrate that Ni domains function as electron reservoir, which transfer electrons to Co and prevent the accumulation of high-valence Co. Besides, the abundant Co/Ni interfaces also facilitate the NO3RR process, thereby achieving a NH3 Faraday efficiency of 99.21%, a NH3 yield rate of 93.55 mg h-1 cm-2, and a NO3RR stability of 120 h. Our analyses delve into the underlying causes of the observed stability of metallic Co in Co6Ni4 and provide compelling evidence that the discrepancy between the adsorption quantity of NO3 - on catalyst surface and the corresponding electron supply is a pivotal factor influencing the reconstruction process.